2020
DOI: 10.1093/infdis/jiaa693
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Factors Associated With High- and Low-Risk Oral Human Papillomavirus Genotypes in Men

Abstract: Background HPV causes oral warts and oropharyngeal cancer (OPC). HPV-attributable OPC incidence among men is significantly increasing worldwide yet few studies have reported oral HPV across multiple countries or examined factors associated with low and high-risk HPV separately. Methods Oral gargles from 3,095 men in the multinational HPV Infection in Men (HIM) Study were HPV genotyped. Multivariable models assessed factors in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
(39 reference statements)
0
1
0
Order By: Relevance
“…However, other studies have found presence of periodontitis to be associated with OPC [ 13 ]. Further, HPV prevalence [ 14 ] and persistence [ 15 ], the precursor to OPC were also associated with periodontitis. Combined, these data indicate that components of dental fitness, including periodontal disease, may be associated with oral HPV persistence, subsequent risk of OPC, and poor treatment outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…However, other studies have found presence of periodontitis to be associated with OPC [ 13 ]. Further, HPV prevalence [ 14 ] and persistence [ 15 ], the precursor to OPC were also associated with periodontitis. Combined, these data indicate that components of dental fitness, including periodontal disease, may be associated with oral HPV persistence, subsequent risk of OPC, and poor treatment outcomes.…”
Section: Introductionmentioning
confidence: 99%